Kebijakan Reforma Agraria Pasca Lahirnya Bank Tanah - Indri Asra Ismanto; Pujiyono; Hari Purwadi (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
In Indonesia, Landeform is a problem that cannot be resolved well. The existence of the Government Regulation of Indonesia Number 64 of 2021 concerning the Land Bank which contains content of Landreform in it. This research will analyze the policies and linkages of Landreform after the existence of the Land Bank. This research uses normative juridical research methods, with a statute approach and library research data collection techniques. This research indicate that the goal of Landreform achievment are to decrease inequality in land ownership in order to create justice and create people's welfare through proportional control of land ownershiop, while the goal of the Land Bank refers to procurement of land for the economy and investment which focuses on country growth and country profits, even though one of the land bank’s purpose is for Landreform, the purpose of Land Bank are too many and non-specific covering public and private interests, so a balance is needed in the implementation of the Landreform.